2023
DOI: 10.1111/1541-4337.13121
|View full text |Cite
|
Sign up to set email alerts
|

Current and future interventions for improving poultry health and poultry food safety and security: A comprehensive review

Abstract: Poultry is thriving across the globe. Chicken meat is the most preferred poultry worldwide, and its popularity is increasing. However, poultry also threatens human hygiene, especially as a fomite of infectious diseases caused by the major foodborne pathogens (Campylobacter, Salmonella, and Listeria). Preventing pathogenic bacterial biofilm is crucial in the chicken industry due to increasing food safety hazards caused by recurring contamination and the rapid degradation of meat, as well as the increased resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
11

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 306 publications
0
22
0
11
Order By: Relevance
“…As shown in Figure 7, meat, poultry, egg products, salads, tuna, chicken, potatoes and macaroni are the main foods that are commonly infected with bacterias (Chowdhury et al, 2023). Foods rich in protein tend to be decomposed by bacteria.…”
Section: Effect Of the Antibacterial And Antioxidant Agent From Natur...mentioning
confidence: 99%
“…As shown in Figure 7, meat, poultry, egg products, salads, tuna, chicken, potatoes and macaroni are the main foods that are commonly infected with bacterias (Chowdhury et al, 2023). Foods rich in protein tend to be decomposed by bacteria.…”
Section: Effect Of the Antibacterial And Antioxidant Agent From Natur...mentioning
confidence: 99%
“…Enteritidis and S . Typhimurium serovars (Chowdhury et al., 2023 ). Therefore, efforts to minimize the prevalence of infection in poultry, which is the primary source for preventing and controlling the Salmonella infection worldwide, are important.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, Salmonella is one of the most important food safety problems in poultry (Havelaar et al, 2015).It is transmitted to humans and animals by consuming water and food contaminated with Salmonella, which is shed from the intestinal tract of rodents, livestock, and humans, especially birds. While Salmonella serovars that cause gastroenteritis cause economic losses to producers by delaying the growth of chickens (Remus et al, 2014), they are considered one of the important public health problems by the European Food Safety Authority because they are the most common causes of acute gastroenteritis in humans, the most common of which are S. Enteritidis and S. Typhimurium serovars (Chowdhury et al, 2023). Therefore, efforts to minimize the prevalence of infection in poultry, which is the primary source for preventing and controlling the Salmonella infection worldwide, are important.…”
mentioning
confidence: 99%
“…Several investigators have studied the effects of EO on chickens under heat stress conditions ( Shehata et al, 2022b ; Yilmaz and Gul, 2023a ; Mangan and Siwek, 2023 ). These studies have shown that EO can improve performance, while reducing the negative outcomes of heat stress, such as reduced water intake, oxidative stress, and inflammation ( Chowdhury et al, 2023 ; Das et al, 2023 ; Rafeeq et al, 2023 ). Some EO have improved the immune system of chickens, which can help reduce the incidence of disease under heat stress conditions ( Perini et al, 2020 ; Ruff et al, 2021 ; Yilmaz and Gul, 2023b ; Jahja et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%